The Kv7 potassium channel activator retigabine decreases alcohol consumption in rats. (May 2014) - Knapp, Clifford M.; O'Malley, Matthew; Datta, Subimal; Ciraulo, Domenic A.
Abstract Background: Activation of Kv7 potassium channels may decrease the reactivity of mesolimbic dopaminergic neurons that are implicated in mediating the reinforcing effects of ethanol. Objectives: The objective of this study was to determine whether the administration of the Kv7 potassium channel opener retigabine would decrease ethanol intake in Long Evans rats. Methods: A limited access two-bottle choice model of alcohol (10% solution) consumption was used in this study. A separate group of animals was tested to evaluate the actions of retigabine on sucrose (5% solution) consumption to determine whether this drug might produce non-selective impairment of the ability of rats to drink liquids. Animals were treated with either vehicle or increasing doses (2.5–7.5 mg/kg SC) of retigabine administered over a 3-day period. Results: Compared to vehicle, retigabine at a dose of 7.5 mg/kg produced a reduction in the amount of ethanol consumed. These effects did not occur in association with significant changes in water consumption. A significant time effect was found for the actions of retigabine in sucrose-drinking rats with a trend for an increase in sucrose intake with the highest dose of retigabine administered. Conclusions: These results indicate that the administration of retigabine may produce a decrease in ethanol consumption by rats at doses that do not significantly reduce the drinking of either water or a sucrose solution. These findings are consistent with the hypothesis that activation of Kv7 channels facilitates the reduction of alcohol consumption in the rat.